PERAN ETNISITAS, DUKUNGAN DAN STATUS SOSIAL ORANGTUA TERHADAP MOTIVASI BERPRESTASI PADA SISWA KETURUNAN TIONGHOA DAN SISWA JAWA - , WANADYA AYU KRISHNA DEWI; , Prof. Dr. Amitya Kumara, MS., Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study was aimed in understanding the role of ethnicity, paental support and parentâs social status on achievement motivation of Indonesian- Chinese and Javanese students. The respondets were taken using purposive sample and obtained 212 respondents (116 as Javanese, 62 as Indonesian Chinese, and 34 as other ethnicity) to fill in two research scales. The scales used in this study are achievement motivation scale, parental support scale, and respondents must fill in a number of questions in order to know the social status of oneâs parents. This study found that there are effects of ethnicity, parental support, parentâs social status simultaneously on the studentâs achievement motivation of students (p=0,000, p<0,01). There is also an effect of ethnicity on achievement motivation among Chinese-Indonesian and Javanese students (p=0,000, p<0,01) whereas the Chinese-Indonesian students had a higher average of achievement motivation than the Javanese as much as 5,236. Another finding showed that there is a significant effect of parental suport on the studentâs achievement motivation (p<0,01), and there is a significant effect of parentâs social status on studentâs achivement motivation, (Fcalculated=5,0003 and Ftable=2,44). This research has proven that ethnicity, parental support and parentâs social status does play a role on the achievement motivation of Chinese- Indonesian and Javanese students.